Community-Based Critical Literacy Practices: A Reflective Study of Literacy Implementation in School - Tono Viono; Jagad Wijaksono; Hasan Busri (Tarbawi : Jurnal Ilmu Pendidikan, 2023)
This article examines critical literacy practices carried out by the informal education community thoughtfully and potentially so that they can be applied to developing the school literacy movement program. Statistically, 95.66% of Indonesia's population can read, but on the other hand, the reading literacy score in the PISA study is still below average. So far, there have been different perspectives regarding literacy as a reading activity and literacy as an activity to process information. These differences result in different interpretations and attitudes in processing information in a text. Critical literacy relates reading analysis skills to the realities faced by students. This study aimed to find patterns of critical literacy carried out by the Ngampar Boekoe community and Jamaah Maiyah Al Manhal about the inherent development of the school literacy movement program. The research method used is qualitative with an auto-ethnographic approach. The data comes from the researcher's personal experience, observation, in-depth interviews and artefacts. Data analysis uses triangulation with a bottom-up pattern to find critical literacy formulas and can be reflected in the school literacy movement program. The results found are in the form of alternative formulations which consist of critical material that can develop students' critical power, dialectical methods filled with a sense of trust, and quality-based evaluation using response journal instruments and written works. The results of this study can be used as policy-making considerations for relevant stakeholders to build the qualifications of a literate society.